Long‐term oxidation stability of gasoline on account of MIR monitoring - Andziulis, Arunas (Transport, 2006)
The problem of oxidation stability of petroleum products often arises under the protracted transportation or tankage of products in the maritime terminal storages or in the national repositories for a prolonged time. So, this paper presents the results of study of auto‐oxidation kinetics of hydrocarbons in the gasoline, carried out by applying the method of middle range IR spectroscopy (MIR) monitoring aimed at the prediction of fuel oxidation stability. The results of study enabled to propose the virtual chemometrical model based on the MIR spectrum analysis which was applicable for testers which register the changes in concentration of olefins. As the object of research there was taken the gasoline which was carrying JV; > 50–90 of different structures of C2‐C10 olefins in unordered set of hydrocarbons which degrade the petroleum product. First Published Online: 27 Oct 2010